Diagnosing cognitive disorders in older adults with epilepsy. (1st December 2020) - Reyes, Anny; Kaestner, Erik; Edmonds, Emily C.; Christina Macari, Anna; Wang, Zhong Irene; Drane, Daniel L.; Punia, Vineet; Busch, Robyn M.; Hermann, Bruce P.; McDonald, Carrie R.; ,
Abstract: Objective: To characterize the nature and prevalence of cognitive disorders in older adults with temporal lobe epilepsy (TLE) and compare their cognitive profiles to patients with amnestic mild cognitive impairment (ie, aMCI). Methods: Seventy‐one older patients with TLE, 77 aMCI, and 69 normal aging controls (NACs), all 55‐80 years of age, completed neuropsychological measures of memory, language, executive function, and processing speed. An actuarial neuropsychological method designed to diagnose MCI was applied to individual patients to identify older adults with TLE who met diagnostic criteria for MCI (TLE‐MCI). A linear classifier was performed to evaluate how well the diagnostic criteria differentiated patients with TLE‐MCI from aMCI. In TLE, the contribution of epilepsy‐related and vascular risk factors to cognitive impairment was evaluated using multiple regression. Results: Forty‐three TLE patients (60%) met criteria for TLE‐MCI, demonstrating marked deficits in both memory and language. When patients were analyzed according to age at seizure onset, 63% of those with an early onset (<50 years) versus 56% of those with late onset (≥ 50 years) met criteria for TLE‐MCI. A classification model between TLE‐MCI and aMCI correctly classified 81.1% (90.6% specificity, 61.3% sensitivity) of the cohort based on neuropsychological scores. Whereas TLE‐MCI showed greater deficits in language relative to aMCI, patients with aMCI showed greater rapid forgetting on memory measures. Both epilepsy‐related risk factors and the presence of leukoaraiosis on MRI contributed to impairment profiles in TLE‐MCI. Significance: Cognitive impairment is a common comorbidity in epilepsy and it presents in a substantial number of older adults with TLE. Although the underlying etiologies are unknown in many patients, the TLE‐MCI phenotype may be secondary to an accumulation of epilepsy and vascular risk factors, signal the onset of a neurodegenerative disease, or represent a combination of factors.